Representations and teaching practices around the Franco dictatorship (Tempo e Argumento, 2021)
In this article we carry out a case study focused on 5 Spanish teachers in relation to their educational approach to the Franco dictatorship. It starts from a general contextualization of the historical period in the Franco dictatorship (1936-39 and 1975-78), a socially and politically hot topic that has its correlate at an educational level as it exists in the curriculum of secondary and high school education. This research focuses on teachers, who translate into the classroom context a series of ideas and representations of the dictatorship, which is conditioned by their educational level, the current socio-political context, and the curricular concretion that is carried out in educational regulations. The representations, knowledge, and practices analyzed with these 5 teachers allow us to identify trends, possibilities, and difficulties in teaching the Franco dictatorship.Keywords: Franco dictatorship; History; History teaching; Teachers.